Sharpening Students' Science Literacy Skills with The Numbered Heads Together Cooperative Model Based on Socio-Scientific Issue - Monica*, Elsa; Suprapto, Nadi; Budiyanto, Mohammad; Sukarmin, Sukarmin; Rini, Sapti Puspita; Cheng, Tsung-Hui (Universitas Syiah Kuala, 2025)
The importance of science literacy skills in the 21st century today can help a person have the knowledge to solve problems in everyday life. Science literacy in society has the potential to help answer unsolved problems related to socio-scientific issue (SSI). Through a teamwork-orientated learning model, this can stimulate students' science literacy skills. The purpose of this study was to stimulate students with the numbered heads together cooperative model with the SSI approach to improve their science literacy skills. The research was conducted by involving 36 students from science education department. The research used quantitative method. The results showed that there were differences before and after learning by using the numbered heads together cooperative model. The results tested by N-Gain analysis showed that the use of cooperative learning model numbered heads together based on SSI can improve students' science literacy skills with an N-Gain score of 0.45 in the medium category